Tujuan utama moderasi beragama perspektif Abdul Malik Karim Amrullah - Diana, Diana; Suhada, Suhada; Rismanto, Muhammad; Utomo, Ainur Alam Budi; Abdullah, Sandy Husein (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
This study identifies and analyzes Buya Hamka’s views on religious moderation. The method used is library research with content analysis. Based on the research results, Buya Hamka’s views on religious moderation emphasize balance, steadfastness, justice, and tolerance. By applying these values, humans must understand and respect each other. Islam teaches a good relationship with God and other humans, where the practice of worship always produces a peaceful attitude towards others. Therefore, the ultimate goal of religious moderation, according to Buya Hamka, is the creation of happiness and peace among people of different beliefs. To actualize this concept of religious moderation, steps that can be taken include: incorporating related materials into formal education, holding seminars or talk shows, supporting content creators who promote diversity, and creating a platform about religious moderation. These steps are important because the millennial generation is very active on social media, allowing the values of peace to be conveyed and felt amidst existing differences.